X-ray absorption spectroscopy of metal site speciation in the metallo-β-lactamase BcII from Bacillus cereus - Breece, Robert M. (2012)
Cobalt and zinc binding by the subclass B1 metallo-beta-lactamase BcII from Bacillus cereus is examined by X-ray absorption spectroscopy, at various levels of metal loading. The data show that a significant amount of the dinuclear enzyme is formed, even at substoichiometric levels of metal loading, whether the added metal is Zn(II) or Co(II). Increasing metal addition, from 0.5 to 1.0 to 2.0 eq/mol of enzyme, are shown to result in a more ordered active site. While Zn(II) appears to show no preference for the Zn1 (3H) or Zn2 (DCH) sites,the extended X-ray absorption fine structure (EXAFS) suggests that Co(II) shows a slight preference for the DCH site at low levels of added Co(II). The results are discussed in the context of similar metal-binding studies of other B1 metallo-beta-lactamases.